One-bit quantization delta-sigma modulation-based autoencoder for power-efficient free-space communication - Cai, Jifan; Lu, Zhilan; Luo, Zhiteng; Zhang, Junwen; Chi, Nan (Optics letters, 2023)
This Letter proposes a novel, to the best of our knowledge, approach utilizing a delta-sigma modulation (DSM)-based 1-bit autoencoder (AE) for efficient encoding and decoding in various channel conditions. Simulation analysis demonstrates the AE's ability to mitigate noise by reducing a peak-to-average power ratio (PAPR) and enhancing an in-band power of the signals, particularly under low signal-to-noise ratios (SNRs). The AE-DSM achieves theoretical transmission performance even at SNRs below 6 dB. In a 40-m free-space link experiment, the AE-DSM exhibits an 8.4-dB lower bit error rate (BER) compared to 64QAM-DSM, enabling a transmission rate of 1.31 Gbps. Furthermore, the 1-bit AE-DSM significantly reduces power consumption in the receiving analog-to-digital converter (ADC), facilitates transmission at low SNRs, and effectively mitigates nonlinear effects. Consequently, the DSM-based AE holds immense potential for future mobile fronthaul links.This Letter proposes a novel, to the best of our knowledge, approach utilizing a delta-sigma modulation (DSM)-based 1-bit autoencoder (AE) for efficient encoding and decoding in various channel conditions. Simulation analysis demonstrates the AE's ability to mitigate noise by reducing a peak-to-average power ratio (PAPR) and enhancing an in-band power of the signals, particularly under low signal-to-noise ratios (SNRs). The AE-DSM achieves theoretical transmission performance even at SNRs below 6 dB. In a 40-m free-space link experiment, the AE-DSM exhibits an 8.4-dB lower bit error rate (BER) compared to 64QAM-DSM, enabling a transmission rate of 1.31 Gbps. Furthermore, the 1-bit AE-DSM significantly reduces power consumption in the receiving analog-to-digital converter (ADC), facilitates transmission at low SNRs, and effectively mitigates nonlinear effects. Consequently, the DSM-based AE holds immense potential for future mobile fronthaul links.